(untitled) (Global Journal of Human-Social Science, 2020)
This article addresses certain interpretations about the origins, character istics and legacies of the protests that took place in mid-June 2013 in Brazil. The qualitative research systematized 55 academic publications about the Journeys of June. The results show that, in general, the Journeys are associated with the protests that took place in the city of Sao Paulo against the increase in bus fares. The Journeys would have expressed popular dissatisfaction with the political system and its ineffectiveness in fulfilling social demands. In addition to presenting such interpretations, the text problematizes some of them, pointing to the diversity of actors, agendas and repertoires of the protests, avoiding certain generalizations present in the researched texts. The research contributes to the knowledge about the 2013 June Journeys in Brazil, based on the conception that these are interpretations and therefore are subject to problematization.